Class imbalance resolution in IoT networks using advanced elk herd optimization with SMOTE and iteratively fine-tuned deep BiLSTM - Srikanth Mudiyanur Sriramappa; Ananda Babu Jayachandra; Vasantha Kumar Mahadevachar; Ashwini Kailas; T. G. Keerthan Kumar (Institute of Advanced Engineering and Science, 2026)
The